Pseudoendoleak: A post‐endovascular aortic repair ultrasound surveillance pitfall – Single institution case series. Issue 8 (10th April 2022) - Lisik, James P; Curry, Greg; Buckenham, Timothy
Abstract: Introduction: In the context of increasingly common endovascular treatment for abdominal aortic aneurysms, endoleak is a relatively common complication of (abdominal) EVAR, and ongoing multimodality surveillance programs are recommended by expert bodies including the Society for Vascular Surgery (SVS). We describe the colour doppler ultrasound (CDUS) finding defined as pseudoendoleak that may be misinterpreted as significant endoleak and may be resolved through the use of contrast‐enhanced ultrasound (CEUS). Methods: Retrospective review of cases at our institution identified five cases where apparent endoleak on CDUS was not evident on CEUS, performed immediately following CDUS. Results: Each of these five cases demonstrated interval increase in sac size at varying intervals post‐EVAR, and in 4 out of 5 cases, no endoleak was demonstrated on multiple other modalities, at multiple time points. One case demonstrated an isolated type 2 endoleak at one time point, a finding that could not be reproduced. In each case, index‐positive CDUS is thought to represent agitated fluid within the excluded sac that is not in continuity with the arterial blood pool as evidenced by the absence of CEUS enhancement. Conclusions: In cases of positive post‐EVAR CDUS, CEUS is an effective tool to exclude the presence of pseudoendoleak and thus avoid further and potentially invasive diagnostic modalities in an elderly and comorbid cohort.